Integrated Smart Patch for Heart Rate and Respiratory Rate Monitoring - Gogola, Daniel; Ackovska, Nevena; Bagín, Richard; Koteska, Bojana; Madevska Bogdanova, Ana; Kostoska, Magdalena; Lehocki, Fedor; Tysler, Milan (IEEE, 2023)
A wearable smart patch was designed to monitor the vital parameters of mass casualties’ victims after the first triage. The device captures ECG, PPG, and respiration signals and triggers an alarm if the heart rate (HR) or respiration rate (RR) exceeds the specified limits and indicates a threat to the victim's life. To obtain a robust and reliable solution, the same parameters are derived from two or three independent signals. In this study, ECG signals have been recorded from different positions on the chest, and the performance of several algorithms for HR and RR extraction was tested. The initial measurements show that HR estimation is more accurate and reliable than RR estimation. The best results, considering both, the HR and RR calculations, were achieved when Pan-Tompkins’s algorithm was used, and ECG electrodes were placed vertically on the right anterior chest. Increasing the length of the evaluated ECG signal above 30 seconds did not significantly affect the HR and RR calculation, regardless of the algorithm used.
Keywords: Wearable Sensors; Monitoring of Vital Parameters; Electrocardiogram; Heart Rate; Respiratory Rate